2019
DOI: 10.21608/jppp.2019.79456
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Secondary Metabolites of Locally Isolated Fungal Strains against some Cotton Insect Pests

Abstract: Microbial pest control is one of the best alternatives to chemical insecticides. Beauveria bassiana and Trichoderma harzianum are important entomopathogens of many insect pests. Cotton leafworm (Spodoptera littoralis) and aphids (Aphis gossypii) are the most destructive pests in crop production such as cotton, cabbage, tomato, potato, and lettuce. The present study sought to isolate both fungal strains (B. bassiana and T. harzianum) and extract their secondary metabolites by ethyl acetate then evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
1
23
0
1
Order By: Relevance
“…These derivatives are reported to be important in personal care products such as hair and skincare, antiperspirants, and deodorants. Their antibacterial, antifungal [ 28 ], insecticidal, antimicrobial [ 36 , 37 ], and preservative properties [ 27 ] have been reported. Six different types of fatty acid esters were identified in both methanol extracts with reported antioxidant, thyroid inhibitor [ 33 ], anticancer [ 34 ], anti-inflammatory [ 32 ], hemolytic, antiandrogenic, lubricant, pesticide, nematicide, hypocholesterolemic [ 30 ], and dienophilic [ 31 ] activities.…”
Section: Resultsmentioning
confidence: 99%
“…These derivatives are reported to be important in personal care products such as hair and skincare, antiperspirants, and deodorants. Their antibacterial, antifungal [ 28 ], insecticidal, antimicrobial [ 36 , 37 ], and preservative properties [ 27 ] have been reported. Six different types of fatty acid esters were identified in both methanol extracts with reported antioxidant, thyroid inhibitor [ 33 ], anticancer [ 34 ], anti-inflammatory [ 32 ], hemolytic, antiandrogenic, lubricant, pesticide, nematicide, hypocholesterolemic [ 30 ], and dienophilic [ 31 ] activities.…”
Section: Resultsmentioning
confidence: 99%
“…A literature survey regarding the biological activities of the phytochemical constituents of our studied extracts in GC–MS profiling Table 2 showed that there are many studies reporting many biological activities of the same obtained constituent in our study from a variety of botanical extracts. Many biological activities including the insecticidal activity are recorded for the following constituents: 9-2-Methyl-Z, Z-3, 13 octadecadienol (terpenoid) which act as a Pesticide, herbicide, insecticide and as a pheromone [ Adeyemi et al, 2017 ], the second constituent: 9,17-Octadecadienal, (Z)- an insecticidal Aldehydecompound and act also as an Antieczemic, Nematicide, Antihistaminic and Antimicrobial [ Oni et al, 2020 ], the third constituent, Nonanoic acid, 9-oxo-, methyl ester a Potent antifungal, Antioxidant, Potent Antimicrobial [ Sen et al, 2017 ] beside its larvicidal activity [ Sen et al, 2017 ], fourthly 9,12-Octadecadienoic acid (Z,Z)- known as linoleic acid a Polyunsaturated Fatty acid which has many activities like Insecticidal activity [ Christiana et al, 2019 ], Anti-inflammatory, Hypocholesterolemic Cancer preventive, Hepatoprotective, Nematicide Insectifuge, Antihistaminic Antieczemic, Antiacne, 5-Alpha reductase inhibitor Antiandrogenic, Antiarthritic and Anticoronary, [ Adeyemi et al, 2017 ] and finally Octasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecamethyl- which has an antimicrobial activity)[ Ahmed et al, 2020 ] beside its insecticidal activity [ Abdullah, 2019 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pathways and mechanisms of fatty acid synthesis in insects, this result may be caused by the enhancement of the activity of key enzymes such as Acetyl CoA carboxylase or fatty acid synthase, leading to a certain degree of lipid accumulation [ 43 , 44 , 45 , 46 ]. Moreover, n-Hexadecanoic acid and Tetradecanoic acid were found to be responsible for the insect growth inhibitory and insecticide activity [ 47 , 48 , 49 , 50 ]. Therefore, irradiation treatment can lead to fatty profile changes and was found to be lethal to treated insects, but the mechanism was more complicated than we expected.…”
Section: Resultsmentioning
confidence: 99%